The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1029/2001ja000214
|View full text |Cite
|
Sign up to set email alerts
|

Global impact of ionospheric outflows on the dynamics of the magnetosphere and cross‐polar cap potential

Abstract: [1] Statistical results for the ionospheric outflows indicate that the ionosphere is an important source of plasma to the magnetosphere. However, the exact consequences on the dynamics of the magnetosphere from this ionospheric outflow have yet to be determined. This issue is taken up in multifluid modeling of the 24-25 September 1998 magnetic cloud event for which strong heavy ionospheric outflows have been previously reported. It is demonstrated that one of the key influences of heavy ionospheric outflows is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
163
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(178 citation statements)
references
References 32 publications
11
163
1
Order By: Relevance
“…This reduction appears to be due to a global reduction in the intensity of the region 1 field-aligned currents and is likely linked to changes in the conductance resulting from the increased plasma density at the low-altitude simulation boundary and its effects on the electron precipitation derived from the LFM precipitation model [Fedder et al, 1995]. As suggested by Winglee et al [2002], another contributing factor may be the mass loading of the magnetosphere by the O + outflow. To isolate this effect, we will have to perform another series of simulations without electron precipitation, i.e., with fixed ionospheric conductance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction appears to be due to a global reduction in the intensity of the region 1 field-aligned currents and is likely linked to changes in the conductance resulting from the increased plasma density at the low-altitude simulation boundary and its effects on the electron precipitation derived from the LFM precipitation model [Fedder et al, 1995]. As suggested by Winglee et al [2002], another contributing factor may be the mass loading of the magnetosphere by the O + outflow. To isolate this effect, we will have to perform another series of simulations without electron precipitation, i.e., with fixed ionospheric conductance.…”
Section: Discussionmentioning
confidence: 99%
“…Winglee et al [2002] used a multifluid model of the magnetosphere and a gravitationally bound source of O + to study the impact of outflows on the magnetosphere during a storm. They found that O + outflows reduce the cross-polar cap potential and the polar cap area.…”
Section: Introductionmentioning
confidence: 99%
“…[86] In this model [Winglee et al, 2002] an increase of driving of the magnetosphere by the solar wind causes an increase in the ionospheric-plasma outflow into the magnetosphere and this plasma mass loads magnetosphere convection, which reduces the potential of the magnetosphere and the ionosphere. The present findings contradict this explanation of polar cap saturation in two manners.…”
Section: A17 Ionospheric-outflow Modelmentioning
confidence: 99%
“…High altitude measurements such as those we present in this paper does not directly deal with this controversy regarding the total outflow, as all observed particles have reached escape energy. Our interest lies in the further energization of escaping particles, and their role in the global circulation of mass and energy in the magnetospheric system (Winglee et al, 2002;Winglee, 2004) as well as the final fate of these ions (Ebihara et al, 2006). Delcourt (1994) found that centrifugal effects could be important near the frontside magnetopause.…”
Section: Introductionmentioning
confidence: 99%